The Organizational Creativity and its Relationship to Crisis Management in the Light of Coronavirus Pandemic - Madouni, Ali (Technium Social Sciences Journal, 2020)
This paper aims to highlight the organizational creativity and how to manage crises, within the global pandemic crisis of 2019. Common that creativity and innovation are considered as core principles for the continuous advance of any organizational structure, through investment in ideas and manners; to modernize and cope with sorts of response to the performant and technological progress and changes, and to increase the competition effectiveness of the organizational structure, correspondingly. In the other hand, as it is typically recognized that any organization is affected by the external changes, conditions and occurrences; in positive or negative sides. Additionally, the essential pillars of such entities lie implicitly in the strong policies and strategies in dealing with such situations, and in maintaining its balance, especially in time of crises, in particular domestic domains, or crises of a global span. Through this presented paper, we target to approach the relationship between the organizational creativity and crisis management in linkage to the current global pandemic crisis ; as we extend the affecting features on the organizational structure creativity, and its communicative activities.